2013
DOI: 10.1080/13691058.2013.785024
|View full text |Cite
|
Sign up to set email alerts
|

‘Migrants fromover there’ or ‘racial minorityhere’? Sexual networks and prevention practices among sub-Saharan African migrants in France

Abstract: Migrants from sub-Saharan Africa bear a disproportionate burden of HIV infection in Europe, with an increasing proportion of them acquiring HIV after migration. This transformation in the epidemic pattern has raised concerns about the sexual mixing and preventive behaviours of migrants. This paper aims at exploring how racial boundaries shape sexual networks and structure prevention practices among migrants from sub-Saharan Africa. Analyses are based on a French survey carried out among 1874 individuals born i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 37 publications
5
18
0
2
Order By: Relevance
“…Subtyping of a large number of samples would be required to determine if the incidence of HIV- 1 non-B variants is increasing over time in the newly diagnosed native population.Kramer (2008) [29] Sexual mixing (sexual partner with differing ethnicity) High risk = 42 % (84 % unprotected), Moderate risk = 59 % (no data), Low risk = 66 % (no data).SD: +++ V: ++ G: ++ OS: ++Convenience sample and social desirability bias Includes both first generation and second generation migrant with no distinction drawn between them in analysis.Lai (2013) [24]Sexual mixing: 50 % of men and 47 % of women reported partners born in different countries. Most partners from a different African country (men 19 %; women 20 %).SD: + V: ++ G: + OS: ++Convenience sample; low response rate (14 %); desirability bias; data does not support some conclusions reached in the discussion.Marsicano et al (2013) [28] Factors associated with epidemiological networks: Country of origin independently associated with the probability of isolates being detected in clusters OR for Italian vs. African origin: 5.3, 95 % CI: 2.2–12.9, P < 0.001; South American vs. African origin: 25.6, 95 % CI: 2.0–162.0, P < 0.001. SD: +++ V: ++ G: ++ OS: +++ARCA database has relative lack of country of origin and risk factor information for some patients which could have weakened the strength of the detected associations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subtyping of a large number of samples would be required to determine if the incidence of HIV- 1 non-B variants is increasing over time in the newly diagnosed native population.Kramer (2008) [29] Sexual mixing (sexual partner with differing ethnicity) High risk = 42 % (84 % unprotected), Moderate risk = 59 % (no data), Low risk = 66 % (no data).SD: +++ V: ++ G: ++ OS: ++Convenience sample and social desirability bias Includes both first generation and second generation migrant with no distinction drawn between them in analysis.Lai (2013) [24]Sexual mixing: 50 % of men and 47 % of women reported partners born in different countries. Most partners from a different African country (men 19 %; women 20 %).SD: + V: ++ G: + OS: ++Convenience sample; low response rate (14 %); desirability bias; data does not support some conclusions reached in the discussion.Marsicano et al (2013) [28] Factors associated with epidemiological networks: Country of origin independently associated with the probability of isolates being detected in clusters OR for Italian vs. African origin: 5.3, 95 % CI: 2.2–12.9, P < 0.001; South American vs. African origin: 25.6, 95 % CI: 2.0–162.0, P < 0.001. SD: +++ V: ++ G: ++ OS: +++ARCA database has relative lack of country of origin and risk factor information for some patients which could have weakened the strength of the detected associations.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly Marisciano et al (2013) reported that 50 % of men and 47 % of women had partners from a different country although most were from another African country [28]. …”
Section: Resultsmentioning
confidence: 99%
“…The preference for African sexual partners, the existence of African sexual networks [16], and a culture of concurrency elevate the risk of HIV-transmission [3, 10]. Among those in a stable relationship, 33.7% had a sexual partner ‘on the side’ in the last year and 73.0% said their last sexual partner was of sub-Saharan African origin.…”
Section: Discussionmentioning
confidence: 99%
“…Also the increased mobility of migrants since the recent economic crisis is not accounted for in official population numbers [15]. Sub-Saharan African migrants who moved from other European countries to Belgium in search for job opportunities quickly become part of the local sexual networks [16], and this may also influence the Belgian HIV epidemic. Therefore, the present study’s objective was to obtain sound HIV prevalence estimates and to identify sub-groups that should be prioritized for HIV prevention through studying a representative sample of the heterogeneous sub-Saharan African migrant communities present in Antwerp city (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Findings on commitment, trust, and reduced pleasure perception with condom use are in line with those of previous studies. Being in a long-term relationship is associated with lower condom use (Marsicano et al, 2013), as is the belief that condom-protected intercourse is less pleasurable (Barrett & Mulugeta, 2010;Higgins & Wang, 2015). In deciding whether to use condoms, pleasure is a more important factor for men than for women (Randolph, Pinkerton, Bogart, Cecil, & Abramson, 2007), which indicates that how condom use affects perceptions of sexual pleasure is based on gender.…”
Section: Discussionmentioning
confidence: 99%